2021
DOI: 10.3389/fphy.2021.779204
|View full text |Cite
|
Sign up to set email alerts
|

Vector Resolved Energy Fluxes and Collisional Energy Losses in Magnetic Nozzle Radiofrequency Plasma Thrusters

Abstract: Energy losses in a magnetic nozzle radiofrequency plasma thruster are investigated to improve the thruster efficiency and are calculated from particle energy losses in fully kinetic simulations. The simulations calculate particle energy fluxes with a vector resolution including the plasma energy lost to the dielectric wall, the plasma beam energy, and the divergent plasma energy in addition to collisional energy losses. As a result, distributions of energy losses in the thruster and the ratios of the energy lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It is noted that the difference in the thrust between the two operating conditions seems to decrease with an increase in the rf power. Previous particle-in-cell and Monte Carlo collision simulations have shown that a quarter of the rf power is consumed by the collisional excitation [42], which would be enhanced by increasing the electron density. Since the ratio of the excitation energy loss to the wall energy loss would increase with the increase in the rf power, the effect of the cusp on the energy loss to the wall is considered to decrease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the difference in the thrust between the two operating conditions seems to decrease with an increase in the rf power. Previous particle-in-cell and Monte Carlo collision simulations have shown that a quarter of the rf power is consumed by the collisional excitation [42], which would be enhanced by increasing the electron density. Since the ratio of the excitation energy loss to the wall energy loss would increase with the increase in the rf power, the effect of the cusp on the energy loss to the wall is considered to decrease.…”
Section: Resultsmentioning
confidence: 99%
“…The direct thrust measurements in early studies showed very poor thruster efficiencies less than a few percent [30][31][32][33][34][35][36], while the performance has been increased based on the abovementioned scientific understandings [37][38][39]. Theoretical, experimental, and numerical studies have suggested that the major reason of the poor performance is the energy and momentum losses to the source wall [40][41][42], which have been reduced by enlarging the source tube diameter, by increasing the magnetic field strength, and by modifying the plasma density profile by the location of the gas injection port [38]. A cusp magnetic field structure has been applied upstream of the rf antenna to reduce the energy loss to the source wall by terminating the plasma by a magnetic wall, which effectively shortens the source length [39].…”
Section: Introductionmentioning
confidence: 99%